Ensino Remoto Emergencial e Ensino de História e Cultura Afro-Brasileira e Africana: documentos orientadores e os materiais didáticos: Emergency Remote Teaching and Teaching of Afro-Brazilian and African History and Culture: guiding documents and teaching materials - Silva Chaves, Taylon; da Silva Pereira, Morgana (Revista Cocar, 2021)
Este artigo analisa o Ensino Remoto Emergencial (ERE) e o ensino de história e cultura africana e afro-brasileira no contexto da pandemia do novo coronavírus a fim de verificar a implementação da temática étnico-racial no currículo escolar. A pesquisa é de cunho qualitativo e de caráter bibliográfico e documental. Os dados revelam que a temática étnico-racial e o Ensino de História e Cultura Africana e Afro-Brasileira apresenta-se de forma ínfima nos documentos e materiais pedagógicos. Conclui-se que é premente a implementação de novas propostas curriculares, capazes de ultrapassar a lógica universalista de abordar as diferenças culturais. Palavras-chave: Ensino Remoto Emergencial (ERE); Ensino de História e Cultura Africana e Afro-Brasileira; Pandemia Abstract This article analyzes Emergency Remote Education (ERE) and the teaching of African and Afro-Brazilian history and culture in the context of the new coronavirus pandemic in order to verify the implementation of the ethnic-racial theme in the school curriculum. The research is qualitative, bibliographic and documental in nature. The data reveal that the ethnic-racial theme and the Teaching of African and Afro-Brazilian History and Culture are presented in a very small way in the documents and teaching materials. It is concluded that it is urgent to implement new curricular proposals, capable of going beyond the universalist logic of addressing cultural differences. Keywords: Emergency Remote Learning (ERE); Teaching African and Afro-Brazilian History and Culture; Pandemic